If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 2x = 7(x + 2) + -6(x + -3) Reorder the terms: 9 + 2x = 7(2 + x) + -6(x + -3) 9 + 2x = (2 * 7 + x * 7) + -6(x + -3) 9 + 2x = (14 + 7x) + -6(x + -3) Reorder the terms: 9 + 2x = 14 + 7x + -6(-3 + x) 9 + 2x = 14 + 7x + (-3 * -6 + x * -6) 9 + 2x = 14 + 7x + (18 + -6x) Reorder the terms: 9 + 2x = 14 + 18 + 7x + -6x Combine like terms: 14 + 18 = 32 9 + 2x = 32 + 7x + -6x Combine like terms: 7x + -6x = 1x 9 + 2x = 32 + 1x Solving 9 + 2x = 32 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 9 + 2x + -1x = 32 + 1x + -1x Combine like terms: 2x + -1x = 1x 9 + 1x = 32 + 1x + -1x Combine like terms: 1x + -1x = 0 9 + 1x = 32 + 0 9 + 1x = 32 Add '-9' to each side of the equation. 9 + -9 + 1x = 32 + -9 Combine like terms: 9 + -9 = 0 0 + 1x = 32 + -9 1x = 32 + -9 Combine like terms: 32 + -9 = 23 1x = 23 Divide each side by '1'. x = 23 Simplifying x = 23
| 3t-8=4t+24 | | -(3-m)=-(7m+3) | | -(x+6)+7=9x+1-10x | | 18+2y-4=9y-14-3y | | 3(x+2)=9x+5-6x+1 | | (5x+4)(6x^2+3x+6)= | | -64+24=-4x+14x | | 1.4x-4.8=0.8x-0.9 | | (x+1)2-36=0 | | -2x+8+3x=-20+8 | | 13-6(x+3)=12-5(x+4) | | n(n+2)=399 | | w-8=0 | | 3.00(20+x)= | | 9x-(3x+30)=12 | | 23+2y-9=11y-14-5Y | | 105n=-140n | | .17(1.2)= | | 4(a-2)=3a | | 22-7x=111 | | -3(t-1)+6t=5t-1 | | 3(x-4)=8x-5-5x | | 7x+2-x=5+5x-2 | | -6x^2-10=0 | | 6x+4=4(x+3) | | -3x+5+4x=-5+22 | | 10=-6x^2 | | 6-4y=11-8y+4y | | 4x^7+6x^2=0 | | 20x-6=50x+12 | | 36-8m=8m-7m | | y+2.5=-8.5-7.6 |